Any context to this question?
Answer:
>
Step-by-step explanation:
On the left side, we divide first: 12/4=3
On the left side, we get 3+13, which equals 16.
On the right side, we also divide first: 22/2=11
On the right side, we get 11+2, which equals 13.
We know that 16 is larger than 13, so
12 ÷ 4 + 13 > 2 + 22 ÷ 2
Hope this helps!
The polynomial p(x)=x^3-6x^2+32p(x)=x 3 −6x 2 +32p, left parenthesis, x, right parenthesis, equals, x, cubed, minus, 6, x, squar
Ray Of Light [21]
Answer:
(x-4)(x-4)(x+2)
Step-by-step explanation:
Given p(x) = x^3-6x^2+32 when it is divided by x - 4, the quotient gives
x^2-2x-8
Q(x) = P(x)/d(x)
x^3-6x^2+32/x- 4 = x^2-2x-8
Factorizing the quotient
x^2-2x-8
x^2-4x+2x-8
x(x-4)+2(x-4)
(x-4)(x+2)
Hence the polynomial as a product if linear terms is (x-4)(x-4)(x+2)
(1,-1)(2,2)
slope = (2 - (-1) / (2 - 1) = 3/1 = 3
y = mx + b
slope(m) = 3
use either of ur points...(2,2)...x = 2 and y = 2
now we sub and find b, the y int
2 = 3(2) + b
2 = 6 + b
2 - 6 = b
-4 = b
so ur equation is : y = 3x - 4